Studies on Bamboo Distribution in North-eastern Region of India - Biswas, S.A.S. (Indian Forester, 1988)
North-eastern region of India comprising the States of Sikkim, West Bengal (North Bengal Himalaya), Arunachal, Assam, Manipur, Meghalaya, Mizoram, Nagaland and Tripura has over 50% of bamboo species of the total species from India i.e. ca. 115. The principal genera are : Arundinaria, Bambusa, Cephalostachyum, Chimonobambusa, Dendrocalamus, Dinochloa, Melocanna and Thamnocalamus etc. The region can be referred as the centre of genetic diversity for the genera; Arundinaria, Bambusa, Cephalostachyum and Dendrocalamus. The present studies based on surveys in different parts of north-eastern region reveal useful information on distributional patterns of bamboos within the region and role of attributing factors such as morphological features, altitudinal variation, soil types, rainfall, temperature and biotic influence, etc. Statistical analysis on the dominance of bamboo taxa in different parts of the region is provided.